Penggunaan Media Poster Pada Mata Pelajaran Bahasa Indonesia Dalam Meningkatkan Minat Baca Siswa Kelas III SD Inpres 3 Tondo - Siti ilma a.badar; Muhammad Aqil; kadek hariana; Muhammad Fasli (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2023)
This classroom action research aims to improve students’ reading interest in the Indonesian language subject for third-grade students at SD Inpres 3 Tondo. The subjects of this study were 25 students, consisting of 9 male and 16 female students. The research was conducted in two cycles, each consisting of four stages: (a) planning, (b) implementation of action, (c) observation, and (d) reflection. The problem addressed in this study was the students’ low reading interest, which affected their participation and understanding of the learning material. To overcome this issue, the researcher implemented the use of poster media as a learning aid. Data were collected through observations of teacher and student activities, as well as written tests to evaluate learning outcomes. The results showed a significant improvement in students’ reading interest. In the first cycle, the classical completeness percentage reached 66%, and in the second cycle, it increased to 81%. Based on these findings, it can be concluded that the use of poster media in Indonesian language learning is effective in enhancing students' reading interest. The poster media made students more engaged and active in the learning process, thereby positively impacting their learning outcomes